PAPR reduction of OFDM signals using iterative processing and carrier interferometry codes - Anwar, Khoirul; Priantoro, Akhmad Unggul; Ando, Kiyotake; Saito, Masato; Hara, Takao; Okada, Minoru; Yamamoto, Heiichi (2004)
Generally peak-to-average power ratio (PAPR) reduction imposes transmission performante degradation or system capacity reduction. This paper proposes a method for reducing the P APR of OFDM signals by combining carrier Interferometry (Cf) spreading code and iterative processing (IP). The proposed method is capable of reducing the PAPR significantly while minimizing the bit error rate (BER) performance degradation. Computer simulation results prove the effectiveness of the proposed method_ Further. the proposed method does not introduce out-of-band interference, which require filtering whose complexity depends on the filtering requirement.